SISTEM INFORMASI PERMINTAAN DAN PENGELOLAAN DATA ALAT TULIS KANTOR PADA KANTOR PENGADILAN NEGERI WATANSOPPENG - Imran, Zul Rachmat (STMIK KHARISMA Makassar, 2023)
Setting up systems within a company will become easier and faster with a computerized system, including setting up an office stationery management system. The number of human resources will influence the need for office stationery in daily work activities. The need for office stationery must be balanced with the provision of adequate stock of office stationery. In monitoring, an application is needed that can be used by employees in companies who want to make requests for office stationery. Seeing this condition, the author provides a solution in the form of creating an application for ordering and managing computerized office stationery because it will make reporting requests for goods from the branch or site easier because the Warehouse Officer can request goods directly from each connected computer. with the Internet network. Using this system will certainly make work easier and digitalized. The research methods used are observation, interviews, and literature study, as well as the system development method using the Waterfall method. The result of this research is the existence of an application can facilitate the work of employees in managing office stationery at the Watansoppeng District Court office